Description of the Don Kalmyks by the First Don Cossack Authors: аn Experiment in Critical Characterization - Artem Yu. Peretyatko (Монголоведение)
Introduction. The presented article is devoted to the complex reconstruction of the syncretic image of the Don Kalmyks formed in the synchronous narratives of Cossack historians and publicists. A systematic analysis of the previous historiographic tradition indicates that the considered range of regional sources has not been sufficiently used in the framework of scientific analysis, which determines favorable prospects for modern research practice that complements the previously obtained epistemological results. Materials and methods. The empirical material introduced into scientific circulation is reconstructed from the published works of E. N. Katelnikov and V. D. Sukhorukov, which are classical regional narratives, characterising the Don historical writing tradition of the 19th century. The methodological basis of the author’s analysis was rationalistic criticism, integrating subjective assessments of the proposed ethnographic concepts and textual deconstruction of specific information from the sources under consideration. In some cases, elements of microhistorical comparative studies were used, based on extra-source knowledge. Results and conclusions. The considered Cossack narratives lack a unified idea of the regional ethnographic space, and the terminological system is constructed in the context of individual research tasks. E. N. Katelnikov and V. D. Sukhorukov form original images of the Don Kalmyks, among whom there are both «neighboring enemies» as well as the lowest social stratum representatives. The Cossack authors clearly see the neighboring Kalmyks as an alien people, endowed with negative traits. This approach determines both the special significance of the presented narratives as synchronous sources characterizing the systemic attitude of the Don Cossacks to their closest neighbors, and the complete unsuitability of the author’s narratives for the ethnographic characterization of the ethnic group in question. The xenophobic texts by Cossack authors significantly influenced the socio-cultural presentation of the Don Kalmyks in the imperial worldview, creating a distorted picture of regional interaction. In the context of this circumstance, a modern researcher of the chosen problem should systematically consider synchronous narrative traditions, forming an objective image of the ethnic dialogue.